Doxorubicin-Tethered Responsive Gold Nanoparticles Facilitate Intracellular Drug Delivery for Overcoming Multidrug Resistance in Cancer Cells - Wang, Feng; Wang, Yu-Cai; Dou, Shuang; Xiong, Meng-Hua; Sun, Tian-Meng; Wang, Jun (ACS nano, 2011)
Multidrug resistance (MDR) is a major impediment to the success of cancer chemotherapy. Through the development of a drug delivery system that tethers doxorubicin onto the surface of gold nanoparticles with a poly(ethylene glycol) spacer via an acid-labile linkage (DOX-Hyd@AuNPs), we have demonstrated that multidrug resistance in cancer cells can be significantly overcome by a combination of highly efficient cellular entry and a responsive intracellular release of doxorubicin from the gold nanoparticles in acidic organelles. DOX-Hyd@AuNPs achieved enhanced drug accumulation and retention in multidrug resistant MCF-7/ADR cancer cells when it was compared with free doxorubicin. It released doxorubicin in response to the pH of acidic organelles following endocytosis, opposite to the noneffective drug release from doxorubicin-tethered gold nanoparticles via the carbamate linkage (DOX-Cbm@AuNPs), which was shown by the recovered fluorescence of doxorubicin from quenching due to the nanosurface energy transfer between the doxorubicinyl groups and the gold nanoparticles. DOX-Hyd@AuNPs therefore significantly enhanced the cytotoxicity of doxorubicin and induced elevated apoptosis of MCF-7/ADR cancer cells. With a combined therapeutic potential and ability to probe drug release, DOX-Hyd@AuNPs represent a model with dual roles in overcoming MDR in cancer cells and probing the intracellular release of drug from its delivery system.